Primary productivity of natural grass ecosystems of the tropics: A reappraisal - Long, Stephen Patrick; García-Moya, Edmundo; Imbamba, Simeon K.; Kamnalrut, Apinan; Piedade, Maria Teresa Fernandez; Scurlock, Jonathan M.O.; Shen, Yunkang Gang; Hall, D. O. (Plant and Soil, 1989)
Studies of net primary production in four contrasting tropical grasslands show that when full account is taken of losses of plant organs above- and below-ground these ecosystems are far more productive than earlier suggested. Previous values have mainly been provided by the International Biological Programme (IBP), where estimates of production were based on a change in vegetation mass alone and would not necessarily have taken full account of organ losses and turnover. Calculation at three of our sites based on estblished methodology using changes in plant mass alone (i.e. that used by the International Biological Programme, IBP) proved to be serious underestimates of when acount was taken of losses simultaneously with measurement of change in plant mass. Accounting for the turnover of material at these three sites resulted in productivities up to five times higher than were obtained using the standard IBP procedure. An emergent C4 grass stand at a fourth site in the Amazon achieved a productivity which approached the maximum recorded for agricultural crops. In this case, productivity values, when organ losses were taken into account, only slightly exceeded that obtained with IBP methods. The findings reported here have wider implications, in prediction of global carbon cycling, remote sensing of plant productivity and impact assessment of conversion to arable cropping systems. © 1989 Kluwer Academic Publishers.